Otomatisasi Pengujian Aplikasi Scraping Profil Pengguna Facebook Menggunakan Selenium - Muhammad Adji Assalmi; Diki Hidayat; Aldiyansyah; Ibnu Solihah Taghalli; Aries Saifudin (CV. Multi Kreasi Media, 2023)
This research describes how to automate testing scraping applications to automatically retrieve Facebook user profile data. In the digital age, data is extremely valuable. Because data can be processed into new knowledge that can be used in all areas of life such as education, business and business. Facebook is a place where a lot of data is stored. Getting data from Facebook is not easy. I need a technique that my bot can use to crawl Facebook pages, retrieve user profile data, and group it by profile category. The technique is to create a bot out of Selenium. The stages of this research process are: Understand the HTML structure of Facebook pages to find patterns in Facebook profile data. A bot is then developed that can open the user's profile page, retrieve the profile data, and parse it against the patterns in her HTML structure on the Facebook page. Experimented on the web at a speed of 20 Mbit/s, the bot was able to retrieve the details of 100 Facebook user profiles of her in 20 minutes.